Biomass in Portugal: Current Uses and New Policies for Bioenergy Development - Gírio, F; Duarte, L.; Silva, L.; Lukasik, R.; Fernando, A.; Nunes, C.; Dias, J.; Almeida, T.; Nicolau, A.; Bernardo, J. (Be sustainable, 2019)
In this issue Europe collaborates to move Sustainable and Resilient Agriculture forward Sustainable Food and Biomass Production on Marginal Soils Camelina and Crambe as European Sources for Medium-Chain Fatty Acids Biomass in Portugal: Current Uses and New Policies for Bioenergy Development Biomass and the Road to a Climate-Neutral Society Enhancing the Knowledge Base for Sustainable EU Policies BBI JU: a High-Impact Initiative Structuring the EU Bio-Based Industries Bio-based Industries Joint Undertaking Recognizing the Position of Biofuels within the RED II Bioenergy with Carbon Capture Storage and Utilization Engineering an Ambitious Energy Future Where Will We Get Our Biojet? Developing Advanced Sustainable Biofuels for Aviation: the BIO4A Approach Sustainable Drop-In Transport Fuels from Hydrothermal Liquefaction of Low Value Urban Feedstocks.